FAKTOR-FAKTOR YANG MENENTUKAN PADA DIMENSI HUMAN CAPITAL COMPETENCIES DALAM PROGRAM SERTIFIKASI GURU SMK NEGERI DI KOTA SEMARANG - Rahman, Agung Herlambang Luthfi; Maesaroh, Maesaroh; Djumiarti, Titik (Journal of Public Policy and Management Review, 2014)
In Undang-undang Nomor 14 Tahun 2005 about teachers and lecturers, that produces some article among others; article 8 mention that teacher must have academic qualifications, competence, a certificate educator, spiritual and physical health, and have the ability manifesting purpose national education.Therefore, certification are mandatory teachers to improve their quality. Certification teacher is granting certificate educator to the teacher who meet the professional. Teacher virtually professional one is having certificate educator who signed college implementer certification. Professional teacher of decisive importance success learning and certificate because they can create learning active, creative, innovative, and fun.Students will be motivated attending school well if method, matter, the props, delivered he pulled and not boring.The fact, a lot of teachers lazy to continue to learn how to teach good.In fact, special development activities teacher many opened as education and training teacher, seminar teacher, financial report methodology of learning, etc. With the certification expected competence teachers are growing and the quality of education be good.After certification, expected teachers could meet in four competency in UUGD Pasal 10 and government regulation of national education standard Pasal 28. Competence are pedagogik competence, educator personality, professional, and socially. However, virtually a lot of teachers unable to meet four competence that.Besides, the fact indicates performance and the teacher is not increasing after joining certification, even inclined to each before certification.Hence, supposed to exist pattern management and supervision sustainable for teachers to boost their quality after certification. This study aims to describe factors in choosing Human Capital Competencies dimensions in the risk of teacher in SMK Negeri of Semarang City. This research used method descriptive qualitative. This subjects in this study consist of 5 (five) main informant. Based on the research result show to explain the phenomenon on Human Capital Competencies dimensions in the certified teacher with the determinant factor, that is: faith and values, skills, experience, the personality, motivation, the emotional, intellectual, and cultural organization. The eight factors are determining the competence of teacher, especially Human Capital Competencies dimensions. The research done to be said overall be eight (8) factors determine in dimension Human Capital Competencies teacher public SMK in the City of Semarang. Conclusions in this study is to know the factors that determine the competence of the teachers and give me a description of a Human Capital Competencies to a teacher, so it can be a study in the implementation of the efforts to improve competence teacher.